Optimized Parameters of SOFC for steady state and transient simulations using interior search algorithm - El-Hay, E.A.; El-Hameed, M.A.; El-Fergany, A.A. (Energy (Oxford), 2019)
A novel application of interior search optimizer (ISO) to define the necessary parameters to model solid-oxide fuel cells (SOFCs) for further studies is presented. Sum of mean squared error (SMSE) is used to formulate the objective function to be optimized by the ISO subject to the validity of predefined constraints. The current study is carried out into two phases: i) under steady-state; various case studies under various operating conditions are demonstrated, and ii) at later stage, scenarios for transient performance of a SOFC system are investigated. In the same context, MATLAB/SIMULINK is used to implement the proposed ISO-based method. A standard proportional-integral (PI)-controller is engaged to the dynamic model to improve its performance during transient disturbances. Transient responses of the stack current and voltage are analyzed due to load changes. Additionally, the hydrogen and oxygen flow rates along hydrogen utilization are investigated. For all test cases, detailed comparisons to other competing recent algorithms such as satin bowerbird algorithm, grasshopper optimizer and genetic algorithm are made to validate the numerical results. It can be emphasized that the comparisons along other demonstrations indicate the viability of the proposed ISO-based method in defining the unknown parameters of the SOFCs efficiently. •Steady-state and dynamic behaviours of SOFC system are investigated.•The proposed methodology is based on interior search optimization algorithm.•Various case studies are demonstrated with necessary validations.•PI-controller to improve the dynamic responses of SOFC system is proposed.